Structural MRI Correlates of Cognitive Event-Related Potentials in Multiple Sclerosis. Issue 5 (September 2018) - Artemiadis, Artemios K.; Anagnostouli, Maria C.; Zalonis, Ioannis G.; Chairopoulos, Konstantinos G.; Triantafyllou, Nikos I.
Abstract : Purpose: Cognitive impairment in multiple sclerosis has been associated with cognitive event-related potentials and MRI abnormalities. This study aims to explore for the first time the association between P300 and MRI in multiple sclerosis. Methods: Fifty-eight relapsing–remitting patients (41.5 ± 10.5 years old, 41 women, disease duration 139.7 ± 84.9 months) and 51 healthy controls were used. Visual P300 responses and a set of 2- or 3-dimensional MRI indices were obtained. Neuropsychological testing and psychological evaluations were also performed. Results: Multiple sclerosis patients had significantly lower P300 amplitude and more prolonged P300 latencies and reaction times than healthy controls. In total, 67.2% of patients were identified with abnormal P300 response. These patients had greater disability and physical fatigue and had lower visuospatial memory scores than those with normal P300 response. Abnormally low P300 amplitude was associated with lower peripheral gray matter volume and was correlated only with normalized frontal horn width and normalized brain volume, after adjusting for age and education. The moderating role of brain reserve was also documented. Conclusions: P300 event-related potential was related to both linear and volumetric MRI markers. Future studies should expand these results in other disease types and longitudinally. Event-related potentials could serve as an ancillary tool for cognitive assessment in multiple sclerosis. Abstract : Supplemental Digital Content is Available in the Text.